HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA DAN TANGAN DENGAN KETEPATAN SMASH PADA ATLET VOLI PUTRI SVC PEKANBARU - Ernawati '; Saripin '; Kristi agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the observations of researchers in the field that the precision of the athletes smash volleyball Pekanbaru SVC has not been so good. Seen at the time of easy smash opponents in the same block, then the ball is not exactly saasaran or balls out. Apart from that smash done by athletes often on the net, easily taken by the opponent, and so forth. The purpose of this study was to look at the relationship between leg muscle explosive power and hand-eye coordination with the precision of a smash in volleyball athletes SVC Pekanbaru. The population in this study were all volleyball athletes SVC Pekanbaru daughter who follow the practice of volleyball totaling 12. Guided by the description contained in the population at the top, then according Sudjana (1996: 5) sampling determined by total sampling, it is given the number of population small and will be made in the sample as well as the players who participated in the training. Thus the sample is taken volleyball players who totaled 12 people. The instrument used to collect data that tests of leg muscle explosive power with power vertical jump test, and hand eye coordination by using tests of throwing catching the ball and accuracy test spike a volleyball with a measuring accuracy as a smash by using the target containing the figures. Data that was obtained in the correlation analysis using simple and multiple produc moment. Based on the results of the study that the results obtained explosive power leg muscles have a relationship with the precision of Smash in athletes volleyball SVC Pekanbaru, then from the results obtained hand-eye coordination have a relationship with the precision of Smash in athletes volleyball SVC Pekanbaru and there is a relationship together -Same between leg muscle explosive power and hand-eye coordination of the accuracy of Smash in Pekanbaru SVC volleyball athletes.Keywords: Explosive Power limb muscles, and Hand Eye Coordination, Accuracy smash